Water rights and legal pluralism: four contexts for negotiation - Bruns, Bryan Randolph; Meinzen-Dick, Ruth S. (Wiley, 2001)
Increasing water scarcity is increasing pressure on water management institutions, particularly in the area of water rights. A common response is to formalise water tenure, one of several options for securing access and resolving conflicts concerning water allocation. This article looks at four contexts where negotiation, self‐governance and concepts of legal pluralism may help improve water resource management. Existing users and potential new users need to negotiate before water resources are developed. Users can participate in forums with authority to solve basin management problems through self‐governance. Negotiated water transfers offer an alternative to water acquisition by expropriation.